Common Fixed Point Theorem in Partially Ordered ℒ-Fuzzy Metric Spaces - R. Saadati; S. Shakeri; L. J. B. Ćirić (Fixed Point Theory and Applications, 2010)
We introduce partially ordered ℒ-fuzzy metric spaces and prove a common fixed point theorem in these spaces.